Cultura colaborativa y su aporte en la gestión administrativa en las secretarias de la entidad financiera Banecuador del cantón Vinces. - Díaz Macías, Meylin Johanna (2021)
The fundamental objective of the case study is to determine the contribution that the collaborative culture has to generate an adequate administrative management in the BanEcuador Financial Institution of the Vinces canton, it is convenient to specify that, the adaptation of this type of culture allows the institutions public, as well as private, are directed in a collaborative and committed environment, and at the same time directing all their efforts towards the achievement of common objectives. In order for the investigation to have been effective, various techniques were used to collect information, reciprocally, a careful observation of the factors and aspects that intervene in each of the entity's departments began, on the other hand, the ease of detailing each one of the pertinent points that take place in each of the variables, without leaving aside the most essential part that is the problem, all this could be developed by the type of descriptive research that was used. The application of the survey to 5 secretaries of the entity with a questionnaire of 8 questions corresponding to the investigative variables gave access to obtain more real data on the problem. In short, the results of the study suggest that organizations that follow an innovative collaboration model have higher productivity, because the organizational culture requires that officials have an effective relationship and communication so that the processes are carried out in a coordinated manner, in effect, establish an adequate administrative management.